INFLUENCE OF OPERATING PERFORMANCE AND MARKET PERFORMANCE AGAINST THE VALUE OF THE COMPANY BY USING VARIABLE INTERVENING CAPITAL STRUCTURE (Case Study on Indonesian Retail Companies Listed on IDX in 2016-2021) - Novia Pita Nisa Wibowo; Teguh Parmono Hadi (Universitas Putera Batam, 2023)
Increasing the value of the company is very important and the main goal for a company. High company value will increase market confidence in company performance and company prospects in the future. This study aims to determine the effect of operating performance and market performance on company value by using the capital structure intervening variable (Case Study on Indonesian Retail Companies listed on the IDX 2016-2021). The method used in the analysis of this research is purposive sampling using the Smart PLS 3.3.9 program. The population in this study are companies listed on the IDX with 11 selected samples. The results of the study using Smart PLS prove that profitability has an influence on leverage, double funding, and firm value. Profitability has no effect on Equity. There is an Influence between Market Value with Leverage, Equity, and Double Funding. There is no Influence between Market Value and Company Value. There is an Influence between Leverage and firm Value. There is no Influence between Equity, dual funding on Firm Value. There is an indirect effect caused by the intervening variable capital structure (leverage) with profitability on firm value.